Optimal Adherence to a Mediterranean Diet May Not Overcome the Deleterious Effects of Low Physical Fitness on Cardiovascular Disease Risk in Adolescents: A Cross-Sectional Pooled Analysis - Garcia-Hermoso, A (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
To examine the combined association of cardiorespiratory fitness (CRF), muscular fitness (MF), and adherence to a Mediterranean diet (MeDiet) on cardiovascular risk in adolescents, a pooled study, including cross-sectional data from two projects [2477 adolescents (1320 girls) aged 12–18 years], was completed. A shuttle run test was used to assess CRF. MF was assessed by the standing-long jump and handgrip tests. Adherence to a MeDiet was assessed by the Kidmed questionnaire. A cardiovascular risk score was computed from the following components: Age and sex, waist circumference, triglycerides, systolic blood pressure, high-density lipoprotein cholesterol (HDL), and glucose. Analysis of covariance showed that participants classified as having optimal (High) adherence to a MeDiet/HighMF/HighCRF, as well those classified as low adherence to a MeDiet/HighMF/HighCRF, had, on average, the lowest cardiovascular risk score (F = 15.6; p < 0.001). In addition, the high adherence to a MeDiet/LowMF/LowCRF group had the highest odds of having a high cardiovascular risk (OR = 7.1; 95% CI: 3.4–15.1; p < 0.001), followed by the low adherence to a MeDiet/LowMF/LowCRF group (OR = 3.7; 95% CI: 2.2–6.3; p < 0.001), high adherence to a MeDiet/HighMF/LowCRF group (OR = 3.1; 95% CI: 1.4–7.0; p = 0.006), and low adherence to a MeDiet/LowMF/HighCRF group (OR = 2.5; 95% CI: 1.5–4.4; p = 0.002) when compared to those with high adherence to a MeDiet/HighMF/HighCRF, after adjustments for potential confounders. In conclusion, our findings showed that, regardless of the MeDiet status, adolescents with low MF and low CRF cumulatively, presented the highest cardiovascular disease risk. Therefore, these findings suggest that the combination of these two fitness components may be beneficial to adolescents’ cardiometabolic profile, independent of MeDiet behaviour. © 2018 by the authors. Licensee MDPI, Basel, Switzerland.